Research of organic agricultural production support in Poland - Minkova, Olha; Kalinichenko, Antonina; Gorb, Oleg (Technology audit and production reserves, 2017)
The features of supporting organic production in Poland are analyzed in the article. Poland is characterized by the largest employment of the population and the number of farms in the organic sector among the countries of Europe. Despite the favorable natural and climatic conditions, the scientific and practical base, significant areas occupied by organic production, the powerful export potential of the country, the proportion of organic operators in the structure of agricultural producers is very low. The main obstacles to the transition to organic principles are the poor development of environmental infrastructure and support from various services of the entire agricultural system. Therefore, the identification of an effective mechanism to support organic agricultural production will increase the level of public administration and contribute to the development of this promising direction. As a result of the research it is established that for the rapid development of organic movement a well-established, transparent, clear regulated system of organic agriculture must be built. The main incentive mechanisms should be: subsidies and subsidies for the transition period, funding of research institutions, consultative and organizational support, advertising, expansion of new technologies, active public activities, the launch of new types of environmental activities, highly developed information technologies in public administration, a powerful legislative framework, an effective system of control and certification. The use of such system support is accompanied by significant volumes of production in the organic sector of Poland, has a stable development trend. An important indicator is the production of environmentally safe products, focused on the conservation of agricultural land. An implementation of a multi-level support system will allow improving and activating the state policy of supporting the Ukrainian producer.